2014
DOI: 10.1111/iej.12241
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance and stress distribution of simulated immature teeth after apexification with mineral trioxide aggregate

Abstract: Restorative protocols alter the fracture resistance and stress distribution of immature teeth after placement of MTA apical plugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 36 publications
2
38
0
1
Order By: Relevance
“…In addition, the loading scenarios investigated lack the complexity that occurs during functional loading in a patient. This resulted in nonlinearity of the load application and its effects , and therefore is a limitation of this study ‐ only one load condition was tested.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the loading scenarios investigated lack the complexity that occurs during functional loading in a patient. This resulted in nonlinearity of the load application and its effects , and therefore is a limitation of this study ‐ only one load condition was tested.…”
Section: Discussionmentioning
confidence: 99%
“…The results of another study showed that the fracture resistance values of teeth restored with fiber post were higher than that both the unprepared group and the group backfilling with gutta‐percha. Similarly, the results of a recent study showed that teeth restored with fiber posts had the higher fracture resistance than that restored with gutta‐percha after apexification with MTA. The findings of the present study were compared with the findings of studies conducted with MTA because there has been no study on fracture resistance of simulated immature teeth with an apical plug using Biodentine.…”
Section: Discussionmentioning
confidence: 48%
“…) or fibre posts (Brito‐Junior et al . ). In the present study, following apexification with MTA or CH of immature teeth with stage of root development 3 and 4, the remainder of the root canal was filled with gutta‐percha and sealer.…”
Section: Discussionmentioning
confidence: 97%
“…This finding was similar to the results of the present study. In the literature, several physical and biomechanical reasons have been considered responsible for reduced fracture strength of teeth during and following root canal treatment such as the loss of coronal hard and pulp tissue from trauma, caries, restorations combined with access preparation to the root canal system, excessive root canal procedures, the use of various canal disinfectants (Sedgley & Messer 1992, H€ ulsmann et al 2003, Al-Jundi 2004, Oliveira et al 2007) and lack of providing adequate support with using composite restorations extending into the root canal (Lawley et al 2004, Wilkinson et al 2007 or fibre posts (Brito-Junior et al 2014). In the present study, following apexification with MTA or CH of immature teeth with stage of root development 3 and 4, the remainder of the root canal was filled with gutta-percha and sealer.…”
Section: Discussionmentioning
confidence: 99%